Association between gingival crevicular fluid prostaglandin E 2 level and preterm low birth weight - Fouzia Tarannum; Mohamed Faizuddin (Wolters Kluwer Medknow Publications, 2012)
Background: Periodontal infections, which serve as a reservoir of inflammatory mediators such prostaglandin E 2 (PGE 2 ), may pose a threat to the fetal-placental unit and cause preterm delivery. Aim: This study was conducted to estimate the PGE 2 levels in gingival crevicular fluid (GCF) and to explore the association between GCF-PGE 2 levels and preterm low birth weight (PLBW). Materials and Methods: Twenty-two pregnant patients were selected for the study. GCF samples were collected from these patients before delivery and again at 1 month after delivery. PGE 2 level was estimated using a commercially available ELISA kit (Neogen™). Results: The mean GCF-PGE 2 level was 5.8 ng/ml before parturition and 5.5 ng/ml after parturition, but the difference was not statistically significant. There was negative correlation between PGE 2 levels and gestational age at birth. Conclusion: The study provides weak evidence that there is correlation between GCF-PGE 2 levels and birth outcome. Further clinical trials with large samples are required to confirm the association between GCF-PGE 2 levels and PLBW.